2018
DOI: 10.1159/000493986
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Neurofilaments May Discriminate Upper Motor Neuron Syndromes: A Pilot Study

Abstract: Background: Patients presenting with upper motor neuron (UMN) signs may widely diverge in prognosis, ranging from amyotrophic lateral sclerosis (ALS) to primary lateral sclerosis (PLS) and hereditary spastic paraplegia (hSP). Neurofilaments are emerging as potential diagnostic and prognostic biomarkers for ALS, but the diagnosis of UMN syndromes still relies mostly on clinical long-term observation and on familiarity or genetic confirmation. Objectives: To test whether phosphorylated neurofilament heavy chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 21 publications
4
14
0
Order By: Relevance
“…For a more detailed overview of studies analysing differential specificities of NFs in serum and CSF see Table 1. In contrast, slowly progressing MNDs such as hereditary spastic paraplegia [73,74], spinal and bulbar muscular atrophy [75], and, possibly, PLS [74] showed close to normal levels of NFs, a finding which can help to rule out ominous conditions such as ALS. Though promising, these results require an inter-laboratory validation and their confirmation in larger patient cohorts.…”
Section: Nfs As Diagnostic Biomarkers In Als and Other Mndsmentioning
confidence: 98%
See 1 more Smart Citation
“…For a more detailed overview of studies analysing differential specificities of NFs in serum and CSF see Table 1. In contrast, slowly progressing MNDs such as hereditary spastic paraplegia [73,74], spinal and bulbar muscular atrophy [75], and, possibly, PLS [74] showed close to normal levels of NFs, a finding which can help to rule out ominous conditions such as ALS. Though promising, these results require an inter-laboratory validation and their confirmation in larger patient cohorts.…”
Section: Nfs As Diagnostic Biomarkers In Als and Other Mndsmentioning
confidence: 98%
“…Cross-sectional levels of NFs are generally measured at different time points from the onset of disease, without full knowledge of their longitudinal behaviour. Of course, the diagnosis of each of these conditions has by itself robust prognostic implications, when compared to ALS [74].…”
Section: Nfs As Prognostic Biomarkers In Als and Other Mndsmentioning
confidence: 99%
“…Almost all the studies investigating both CSF and blood compartments on ALS patients have showed high correlation between CSF and blood Nfs concentrations, with increased Nfs levels than in blood [7,8,9,10,11,12,13].…”
Section: Csf and Blood Neurofilaments As Biomarkers In Alsmentioning
confidence: 99%
“…The most relevant finding of the study lead by Zucchi et al was that CSF and serum p-NfH can discriminate ALS with predominant UMN signs from other UMN syndromes, like hereditary spastic paraplegia (hSP) and primary lateral sclerosis (PLS); moreover, CSF p-NfH concentration may differentiate UMN syndromes from HC and are the most stronger predictors of survivals [9].…”
Section: Phosphorylated Neurofilament Heavy Chain (P-nfh)mentioning
confidence: 99%
“…13 Furthermore, elevated CSF levels of phosphorylated neurofilament heavy chain in patients with HSP (n = 9) compared with controls have been reported in a previous study. 14 It will be interesting to study NFL levels in patients with ALS harboring KIF5A mutations.…”
Section: Discussionmentioning
confidence: 99%